HIDDEN FEATURES DETECTION USING HISTOGRAM MODIFICATION IN MRI IMAGES - Essa, Samar O (Al-Nahrain Journal of Science, 2010)
Magnetic Resonance Imaging (MRI) uses magnetization and radio waves, rather than x-rays tomake very detailed, cross- sectional pictures of the brain. In this work we are going to explain someprocedures belongs contrast and brightness improvement which is very important in theimprovement the image quality such as the manipulation with the image histogram. Its has beenexplained in this worked “the histogram shrink i.e. reducing the size of the gray level gives a dimlow contrast picture is produced, where, the histogram stretching of the gray level was distributedon a wide scale but there is no increase in the number of pixels in the bright region. The histogramequalization has also been discuss together with its effects of the improvement of the image clarity